Possible abilities of dietary factors to prevent and treat diabetes via the stimulation of glucagon‐like peptide‐1 secretion. Issue 7 (7th April 2015) - Tsuda, Takanori
<x xml:space="preserve">Abstract</x> There is a pressing need for countermeasures against diabetes, which has increased in incidence, becoming a global issue. Glucagon‐like peptide‐1 (GLP‐1), a molecule secreted in enteroendocrine L cells in the lower small and large intestines, is thought to be one of the most important molecular targets for the prevention and treatment of diabetes. There has been increasing interest in the possible ability of dietary factors to treat diabetes via modulating GLP‐1 secretion. There is thought to be a close relationship between incretin and diet, and the purported best approach for using dietary factors to increase GLP‐1 activity is promotion of secretion of endogenous GLP‐1. It have been reported that nutrients as well as various non‐nutrient dietary factors can function as GLP‐1 secretogogues. Here, we present our findings on the GLP‐1 secretion‐stimulating functions of two dietary factors, curcumin and extract of edible sweet potato leaves, which contain caffeoylquinic acid derivatives. However, it is necessary to reveal in greater detail the stimulation of GLP‐1 secretion by dietary factors for preventing and treating diabetes. It is desirable to clarify the exact GLP‐1 secretory pathway, the effect of metabolites derived from dietary factors in gut lumen, and the relationship between incretin and meal.